Austerity, sanctions, and the rise of food banks in the UK. (8th April 2015) - Loopstra, Rachel; Reeves, Aaron; Taylor-Robinson, David; Barr, Ben; McKee, Martin; Stuckler, David
Abstract : Doctors are witnessing increasing numbers of patients seeking referrals to food banks in the United Kingdom. Rachel Loopstra and colleagues ask, is this due to supply or demand?